Development of a platform to align education and practice: bridging Academia and the profession in Portugal - Alves da Costa, Filipa (2022)
Limited fitness for practice may result from a mismatch between education and practice. Aiming to meet the common interests of academics and practitioners, the Portuguese Pharmaceutical Society (PPS) developed the Education and Practice Platform (EPP). The EPP includes one representative from each pharmacy faculty, and all Councils of Speciality Boards of Practice. Brainstorming with involved parties enabled sharing of interests, concerns and identifying a common path. Aims, mission, vision and values were set. The EPP's mission is to: act as an enabler to foster the quality and adequacy of education through sharing best practices, ultimately leading to facilitate professional integration, and to foster quality development in teaching practices with recognition for autonomy in freedom to teach and to learn. Its vision is an alignment of education and practice with the PPS' statutes to ensure validation of the competences defined for each practice area, and compliance with international guidance. Key performance indicators (KPIs) were set. Activities developed include the creation of a national forum to discuss education and practice, development of workshops on teaching methods and pharmacy internships, enhanced representation in international events and response to global and national requests. Ongoing work focuses on the creation of a common training framework in hospital and community pharmacy practice adapted to Portugal. The EPP is a worldwide case study, encouraging the development of discussion contributing to an open climate of sharing best practices, indirectly leading to foster a better alignment between education and practice. Many of these results are so far intangible in scientific terms but worth describing.